(untitled) (Ibrahim Cardiac Medical Journal, 2018)
Background & objective: To evaluate the effectiveness and safety of 0.2% povidone iodine renal pelvic instillation as minimally invasive therapy for chyluria resistant to conservative treatment. Materials & Methods: From July 2015 to December 2016, 9 patients with chyluria were treated. There were 2 males and 7 females ranging from 30-65 years age. Cystoscopic localization of chylous efflux was done. On a day care basis under local anesthesia a 5 Fr open-ended ureteric catheter was introduced on the affected side. Freshly prepared 10 ml 0.2% Povidone iodine solution was instilled as a sclerosing agent in the renal pelvis. A total of 3 doses were given at 8-hour intervals. Unilateral instillation was done in 8 cases, and bilateral instillation was done in 1 patient. Results: Eight of 9 patients showed complete clearance. In 1 patient, recurrence was noted and a repeat injection was given after 4 weeks, with success. Conclusion: Our experience shows that povidone iodine is a safe and effective sclerosing agent in the management of chyluria. Ibrahim Card Med J 2016; 6 (1&2): 41-44